Decreased expression of caspase3 in penis and prostate tissues of rat after the treatment with buceng (Pimpinella alpina Molk &Euricoma longifolia Jack) (Faculty of Medicine Universitas Indonesia, 2013)
Background: Buceng combination of pasak bumi (Eurycoma longifolia Jack) and purwoceng (Pimpinella alpine Molk) has been proven to increase testosterone (Te) level and decrease apoptosis. Unfortunately, there is no evidence whether these effects are mediated by the declining of caspase3. Objective of this study was to evaluate whether buceng could decrease the expression of caspase3 of penis and prostate cells in Sprague Dawley male rats. Methods: Twenty four Sprague Dawley male rats weighing 300 g (90 days old) were randomly assigned into 4 groups of 6 male rats. Group A, rats were castrated and received buceng 50 mg. Group B, rats were not castrated, sacrifices as positive control. Group C, rats were castrated and given 2 mL aquadest as negative control. Group D, rats were castrated and got of 6.75 mg mesterolone, dissolved in 2 mL water. MANOVA statistical analysis was adopted to examine the difference expression of caspase3 in all groups. The comparison of caspase3 expression between two groups exhibiting difference values were evaluated by Post Hoc test. Results: MANOVA revealed statistically significant differences in the expression of caspase3 of penis and prostate tissues among the four groups. Post Hoct test also indicated that expression of caspase3 in group A (buceng) (33.56; 35.83) was significantly lower compared to group C (negative control) (54.33; 60.07) and group D (mesterolone) (51.91;56.21), p = 0.000, and higher compared than group B or normal rats (29.40; 27.72), but statistically not significant (p = 0.826). Conclusion: The treatment of 50 mg buceng/day for 30 consecutive days could decrease caspase3 expression in penis and prostate cells. (Med J Indones. 2013;22:2-8) Keywords: Apoptosis, buceng (Pimpinella alpine Molk – Eurycoma longifolia Jack), caspase3